2013
DOI: 10.1039/c3md00080j
|View full text |Cite
|
Sign up to set email alerts
|

A bivalent ligand targeting the putative mu opioid receptor and chemokine receptor CCR5 heterodimer: binding affinity versus functional activities

Abstract: Opioid substitution and antiretroviral therapies have steadily increased the life spans of AIDS patients with opioid addiction, while the adverse drug-drug interactions and persistence of HIV-associated neurocognitive disorders still require new strategies to target opioid abuse and HIV-1 comorbidities. A bivalent ligand 1 with a 21-atom spacer was thus synthesized and explicitly characterized as a novel pharmacological probe to study the underlying mechanism of opioid-enhanced NeuroAIDS. The steric hindrance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…, Rashid et al 2007, Gomes et al 2013); (iv) bind ligand(s) that differ (e.g. also at allosteric binding sites) (Durroux 2005); (v) bind artificial ligands that modify signaling pathways such as bivalent ligands (Shonberg et al 2011, Mohr et al 2013, Yuan et al 2013.…”
Section: Figurementioning
confidence: 99%
“…, Rashid et al 2007, Gomes et al 2013); (iv) bind ligand(s) that differ (e.g. also at allosteric binding sites) (Durroux 2005); (v) bind artificial ligands that modify signaling pathways such as bivalent ligands (Shonberg et al 2011, Mohr et al 2013, Yuan et al 2013.…”
Section: Figurementioning
confidence: 99%
“…Some in vitro studies have demonstrated that CCR5 and the mu-opioid receptor, both members of the GPCR family, may engage in cross-talk through dimerization (Chen et al, 2004;Yuan et al 2013). These results suggest that CCR5 might be involved in the development of opioid effectiveness, which, to the best of our knowledge, has not been studied in neuropathic pain.…”
Section: Introductionmentioning
confidence: 97%
“…Table 1 shows the results of both CCR5 and MOR radiobinding assays for selected compounds. Within the MOR binding assay, all of the compounds showed higher K i values than naltrexone ( 28 ) [75]. The bivalent compound 22 had a 70-fold loss in binding affinity to the MOR, whereas the monovalent compound 24 had a 13-fold loss in affinity.…”
Section: Chemokine Receptor Bivalent Ligandsmentioning
confidence: 99%
“…The bivalent compound 22 had a 70-fold loss in binding affinity to the MOR, whereas the monovalent compound 24 had a 13-fold loss in affinity. The data for the CCR5 binding assay indicated that any substitution on maraviroc’s phenyl ring is detrimental; there was a clear trend of decreasing affinity with increasing size of the group at the 4-position [75]. Overall, there was about a 1000-fold loss of affinity seen for 22 compared to maraviroc [75].…”
Section: Chemokine Receptor Bivalent Ligandsmentioning
confidence: 99%
See 1 more Smart Citation